2019
DOI: 10.23887/jet.v2i2.16181
|View full text |Cite
|
Sign up to set email alerts
|

Konten Dan Konteks Budaya Lokal Ngada Sebagai Bahan Ajar Tematik Di Sekolah Dasar

Abstract: enelitian ini bertujuan untuk mengetahui macam-macam budaya lokal Ngada yang dapat diintegrasikan dalam materi tematikdi Sekolah Dasar. Subjek dalam penelitian ini adalah materi tematikSekolah Dasar di Kabupaten Ngada.Sedangkan objek yangditeliti adalah konten dan konteks budaya lokal Ngada. Data dalam penelitian ini dikumpulkan dengan menggunakan metodeobservasi dan wawancara. Data dianalisis melalui beberapa tahap, yaitu (1) pengumpulan data, (2) reduksi data, (3) penyajiandata, serta (4) penarikan simpulan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 1 publication
0
10
0
11
Order By: Relevance
“…Previous research revealed the integration of local culture in learning (Saliman, 2007;Suastra, 2010;Tandililing, 2013;Baka, Laksana, & Dhiu, 2018;Ilhami, Riandi, & Sriyati, 2019). Suastra (2010) analyzed the needs of junior high school students, which was used as a basis in designing Balinese culture-based science learning models.…”
Section: Introduction ~mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research revealed the integration of local culture in learning (Saliman, 2007;Suastra, 2010;Tandililing, 2013;Baka, Laksana, & Dhiu, 2018;Ilhami, Riandi, & Sriyati, 2019). Suastra (2010) analyzed the needs of junior high school students, which was used as a basis in designing Balinese culture-based science learning models.…”
Section: Introduction ~mentioning
confidence: 99%
“…Tandililing (2013) developed mathematics learning based on local culture in West Kalimantan (ethnomathematics) in primary schools. Baka, Laksana, & Dhiu (2018) examined the integration of the local culture of Ngada (East Nusa Tenggara) in thematic material in primary schools.…”
Section: Introduction ~mentioning
confidence: 99%
“…Dalam melaksanakan proses pembelajaran yang dilakukan guru dan siswa tidak terlepas dari penggunaan bahan ajar (Anisah & Lastuti, 2018;Jazuli et al, 2018). Bahan ajar pada hakikatnya adalah isi dari mata pelajaran atau bidang studi yang diberikan kepada siswa sesuai dengan kurikulum yang digunakan (Baka et al, 2018;Martha & Andini, 2019). Bahan ajar yang digunakan guru untuk menyampaikan materi kepada siswa, sehingga tujuan pembelajaran dapat tercapai dengan semestinya yang telah dirancang oleh guru (Hidayah & Priscylio, 2019;Rostikawati & Permanasari, 2016).…”
Section: Pembahasanunclassified
“…Local culture is human knowledge as social beings whose contents are tools or models of knowledge that are collectively used by their supporters to interpret and understand the environment they face and are used as references and guidelines for action (Baka et al, 2019); (Wahab, 2019). Thematic learning based on local culture is a systematic learning and facilitates the learning process.…”
Section: Introductionmentioning
confidence: 99%